Induction role of chitosan nanoparticles to Anethum graveolens extract against food-borne bacteria, oxidant, and diabetic activities in vitro - Mashraqi, Abdullah (Frontiers in Microbiology, 2023)
Foodborne diseases as well as Foodborne pathogens are a global issue with significant effects on human health and economy. Therefore, several investigators have tried to find new alternative approaches to prevent and control this problem. In this context, the present study aimed to find some possible and effective approaches for controlling food-borne bacteria via Dill (Anethum graveolens L.) extract (DE) loaded with chitosan nanoparticles (ChNPs) besides its anti-oxidant and anti-diabetic activities. Flavonoid and phenolic contents of DE were detected by HPLC, indicating the presence of 18 constituents, high content (22526.51 µg/mL) of chlorogenic acid, followed by 2236.21 µg/mL of coumaric acid and 2113.81 µg/mL of pyrocatechol. In contrast, low contents of cinnamic acid, methyl gallate, apigenin, daidzein, quercetin, syringic acid, and kaempferol were detected. B. cereus, Staphylococcus aureus, E. coli, S. typhi, E. faecalis, and C. albicans were highly inhibited by DE loaded ChNPs (DELChNPs) with inhibition zones (IZs) of 28.50±0.87, 30.33±0.58, 29.33±0.58, 23.17±0.76, 25.76±0.58, and 24.17±0.29 mm with MIC 15.41±0.36, 7.70±0.17, 15.58±0.07, 31.08±0.07, 31.04±0.07 and 62.33±0.29 µg/mL compared with inhibitory activity caused by DE, where the IZs were 25.83±1.44, 29.67±0.85, 24.83±0.76, 20.33±1.53, 21.17±0.29, and 19.67±1.15 mm with MIC 62.33±0.29, 31.08±0.07, 62.50±0.29, 31.08±0.07, 31.04±0.07, and 249.0±1.73 µg/mL, respectively. Also, the MBC of DELChNPs was less than DE against all tested microorganisms. The MBC/MIC index documented that DELChNPs were more effective than DE. The biofilm of tested bacteria was inhibited by DE and DELChNPs but with different levels of anti-biofilm activity. For example, the anti-biofilm activity was 79.26% and 86.15 % against B. cereus using DE and DELChNPs, respectively. DELChNPs and DE, compared with the ascorbic acid, exhibited DPPH scavenging % with IC50 values of 7.8 µg/mL, 13.96 µg/mL, and 4.83 µg/mL, respectively. Anti-diabetic activity in vitro via inhibition of amylase indicated that IC50 was 164.2µg/mL and 164.3 µg/mL using DE and DELChNPs, respectively. This investigation highlights the vital DE phytoconstituents, particularly DELChNPs which possess important therapeutic effects against food-borne microorganisms and could be utilized as a safe alternative to synthetic drugs.